Pilgrims and travellers in search of the holy - Gothóni, René (Peter Lang, 2010)
Pilgrimage : three theoretical Interpretations / René Gothóni -- Pilgrimage and the blessings of place-making : reflections on and beyond the anthropology of pilgrimage / Simon Coleman -- In search of learning and holiness : Scandinavians going abroad from the Middle Ages to the present / Jakob Christensson -- In the sphere of the holy : pilgrimage to a contemporary Greek convent / Mari-Johanna Rahkala -- St. Petersburg Datsan : the northernmost Buddhist temple in Europe / Alexandre I. Andreyev -- Pilgrimage as business in traditional India / Klaus Karttunen -- Pouring water on Śiva : the case of Tarakeswar pilgrims / Rikka Uuksulainen -- The way is the goal : Buddhist circulatory pilgrimage in Japan with special reference to selected artefacts / Michael Pye -- Traditional Tibetan pilgrimage and the eight holy sites of Rebgong / Wuqi Chenaktsang -- A dead man's pilgrimage : the legend of the Wutun people in Amdo / Juha A. Janhunen -- Tourism, pilgrimage, and the fluidity of material culture in Labrang/Xiahe / Juha Komppa -- Tibetan Buddhist nuns : Damcho Pema's prostrating pilgrimage to Lhasa / Lhundrub Dorji -- Some remarks on understanding the motives of Tibetan nuns / Mitra Hirkinen